Sistema eletrônico para validação da aferição e calibração dos tonômetros tipo Goldmann - Oliveira, Amaro Aparecido de [UNIFESP] (2016)
The purpose of this study was to develop a digital device for the assessment of accuracy of the Goldmann tonometer for calibration purposes. The current method uses a graded metal rod attached to the tonometer where a correlation between its displacement and the pressure exerted by the human eye is verified. The physical variable (pressure) was measured by an indirect non-invasive sensor. Analog signals received by the equipment were converted into digital information and shown in an alphanumeric display. This study showed the potential development of a digital device for calibration of Goldmann tonometers. The results may also serve as basis for creation of new policies for measurement control and calibration of tonometers in Brazil.